Linked sociopolitical and environmental controls on large-scale water conservation program feasibility and effectiveness - Mason, Seth J. K., author; Grigg, Neil, advisor; Thomas, Bradley, committee member; Conrad, Steven A., committee member; Simske, Steve, committee member; Hoag, Dana, committee member (Colorado State University. Libraries, 2025)
Persistent drought in the Colorado River Basin over the last quarter century continues to strain existing water supplies and challenges the effective management of storage reservoirs and water delivery systems. Projections for the future suggest that these challenges are unlikely to abate. Expected outcomes of changing climate throughout the 21st century include elevated air temperatures and declining snowmelt runoff. Reductions in runoff will limit water storage in reservoirs. At the same time, increased evaporative crop use will increase agricultural water demands. These dramatic and opposing shifts in water availability and water demand portend a period of increasing water scarcity and conflict. Water users in the Colorado River Basin desperately need access to new strategies for managing increasingly constrained supplies. The body of research described here probes the diverse attitudinal, sociodemographic and geographical characteristics that moderate or enhance agricultural water conservation effectiveness at the regional scale. Three attendant lines of inquiry explore the social and environmental dimensions of water conservation effectiveness in the Upper Colorado River Basin (UCRB). The first line of inquiry explores aspects of the physical-environmental subsystem that moderate the effectiveness of conservation at the field-scale. The second line of inquiry explores the human-behavioral subsystem that controls the likelihood of water user participation in conservation programs. The third line of inquiry integrates outcomes of research into the physical-environmental and human-behavioral subsystems to evaluate potential water conservation outcomes among networks of water users at the basin scale over the long-term. Each line of inquiry utilizes data and information collected across the West Slope region of Colorado, USA. Research into the physical-environmental controls on conservation outcomes demonstrates how measurable geographical characteristics like soil type and elevation influence patterns of potential consumptive water use reductions under common deficit irrigation practices. Results from a Bayesian hierarchical modeling evaluation of remotely sensed evapotranspiration data show that water savings generated through conservation are highly dependent on elevation and crop type. Notably, conservation on high-elevation grass pasture, a dominant cropping pattern in the UCRB, is significantly less effective at generating meaningful reductions in consumptive water use than on low elevation fields growing other crops. This is particularly evident for conservation strategies that do not require full season irrigation curtailment. Research into the human-behavioral controls on conservation program participation demonstrates that attitudes toward conservation and tendencies toward risk aversion play a dominant role in driving potential adoption rates among agricultural water users. An exploration of the relationship between attitudes and intention to participate in conservation identified a general, widespread resistance to conservation associated with a low sense of individual responsibility to act and a limited sense of agency in contributing meaningfully to basin-scale water management issues. Analysis of Discrete Choice Experiment results suggest that agricultural water users prefer conservation programs that do not require irrigation curtailment on large fractions of their irrigated lands for the entire irrigation season and that matching West Slope water conservation with reductions in transmountain water diversions to Colorado's Front Ranch may help boost participation rates. An agent-based framework integrates modeling tools that characterize the physical-environmental and human-behavioral subsystems and explores emergent behaviors among networks of water users distributed across diverse geographies at the basin scale and over the long-term. Monte Carlo simulation results illustrate trade-offs in conservation policy effectiveness and the uncertainty in outcomes associated with any given policy. The most effective policy pathway for generating meaningful amounts of conserved water appears to be one that includes moderate compensation rates (e.g. $600/acre), requires commitment of at least 50% of an irrigated acreage to full season irrigation curtailment, and includes provisions for a 1:1 match of water conserved on the West Slope with forgone transmountain water diversions to the Front Range. The insights and modeling tools generated here should support data-driven water conservation policy development in the UCRB.
Keywords: behavior modeling; hierarchical Bayesian modeling; water conservation; evapotranspiration; agent based modeling; Upper Colorado River basin